Peran Pelatihan dan Pengembangan dalam Kinerja Karyawan - Farid Al Farizi; Thijanul Aroby; Muhammad Alkirom Wildan (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Human resource training and development are important elements in HR management that play a significant role in improving employee performance and organizational competitiveness. This article discusses the concept of training and development, and how both contribute to building employee competencies and skills. Training focuses on improving short-term capabilities, while development is oriented towards long-term learning to prepare employees for future challenges. Based on literature analysis and previous research, it was found that effective training can reduce turnover and increase employee motivation, productivity, and job satisfaction. To maximize the results, organizations need to implement a strategy for identifying training needs, adjusting programs to the organization's vision, and using a variety of learning models. Thus, planned and sustainable training and development are expected to create an adaptive and productive work environment, thereby supporting the achievement of organizational goals.